Socio-environmental indicators for dengue surveillance in the local level - Flauzino, Regina Fernandes; Souza-Santos, Reinaldo; Oliveira, Rosely Magalhães de (Saúde e Sociedade, 2011)
This paper characterizes a local area in terms of sanitary conditions and environmental degradation processes that may be related to dengue transmission, and discusses the construction of new social and environmental indicators aiming at epidemiological surveillance. The studied area was Ilha da Conceição, in the municipality of Niterói, state of Rio de Janeiro. Key informants were interviewed to obtain information that could be used in the construction of new indicators. Comparing the data from the IBGE with those provided by the informants, we found some differences. The data provided by the latter are more reliable regarding the local reality, and they enable, according to the area, the observation of different modus operandi of garbage collection and public cleansing. The cases were concentrated on flat slum and hill slum areas. It was concluded that it is important to analyze indicators referring to the frequency of water supply and garbage collection in local level studies associated with the incidence of dengue.